(untitled) (International Journal of Sustainable Development & World Policy, 2019)
This study seeks to examine the relationship between government borrowing behaviour and private sector growth in Nigeria. It utilises the Structural Vector Auto-regressions (SVAR) model to analyse the dynamics of government borrowing behaviour on the growth of private sector in Nigeria. The results from impulse response functions and variance decomposition appear to provide evidence that government borrowing behaviour has the tendency of impacting negatively on the effectiveness of private sector grow in Nigeria. This result can be explained, based on the fact that government has higher capacity to borrow than the private sector and this tends to crowd-out private sector in mobilising funds for investment and thus impacted negatively on their capacity to grow. The study, therefore, recommends that both fiscal and monetary authorities should improve on measures and policies that could enhance private sector growth, as higher government debt could create burden for future generations, disrupt movements in interest and exchange rates as well as hinder private investment. Doing this has the potentials of improving performance of private sector and the aggregate economy in Nigeria, since empirical literature is replete with evidence of existence of these channels.